Research on hydrogen induced cracking behavior and service performance of metal pipeline material - Jia, Yongjun; Xue, He; Wang, Zheng (Frontiers in Materials, 2025)
This study systematically investigates the fracture behavior of X80 pipeline steel welded joints under hydrogen-induced cracking (HIC) conditions through combined experimental characterization and numerical simulation. Microstructural observations and Vickers hardness testing reveal significant heterogeneity in the base metal, heat-affected zone (HAZ), and weld metal (WM), resulting in spatially non-uniform mechanical properties. A user-defined subroutine (USDFLD) was employed to assign continuous material property distributions within the finite element model, accurately capturing mechanical heterogeneity and its influence on crack-tip mechanical fields and crack propagation paths. Results show that welding thermal cycles induce pronounced microstructural evolution, significantly altering hardness and strength distributions, which in turn affect the evolution of crack-tip stress and plastic strain fields. Crack propagation preferentially occurs toward regions of higher yield strength, where limited plasticity leads to intensified crack-tip stress concentration, accelerating crack growth and extending propagation paths. Moreover, crack growth is accompanied by local unloading near the crack tip, reducing peak stress and strain compared to the initial stationary crack tip. The stress and strain field reconfiguration are primarily localized near the crack tip, while the far-field mechanical response remains largely stable.